If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + -6y = -6 Solving -1x + -6y = -6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6y' to each side of the equation. -1x + -6y + 6y = -6 + 6y Combine like terms: -6y + 6y = 0 -1x + 0 = -6 + 6y -1x = -6 + 6y Divide each side by '-1'. x = 6 + -6y Simplifying x = 6 + -6y
| 4(x-1)+x=5(x-1)+9 | | 12-2x=6+x | | 3m(5+5)=2m+7 | | 25n-144=256 | | X^3+6x-11=0 | | 4(x+5)-17=76 | | 16-x=45+10 | | 10x+5=205+5x | | 4x-5=-2x+1 | | 2y^2-7=121 | | x*x=-7 | | X^1+6x-11=0 | | 5x+2x+10+3x=2x+x+20+2x | | u/9=9# | | 7x+37=86 | | -2.7=.6x | | ln(x-4)-ln(18)=ln(12) | | 4f-2=14 | | v/10=6 | | 18x-48=15x+24 | | 4p^2-8=-10 | | =12(tanx+2sinx) | | 2W=2/3(6W-12)=4W | | (X-3)2+(y-2)2=9 | | 4p^2-9x-2=0 | | c+12(5)=2c | | X*X+V=W*W | | 3x-68=19 | | -18=6 | | 3x^2-56=2x | | rm+6.2=8.9 | | (-3)+(-17)= |